Synthesis and in vitro drug release of primaquine phosphate loaded PLGA nanoparticles - Patel, Bharat; Tripathi, Satyendra Kumar; Pathak, Sandhya; Shukla, Sandeep; Pandey, Archna (European Journal of Chemistry, 2021)
Plasmodium falciparum is one of the most common resistant Plasmodium species responsible for high rates of morbidity and mortality in malaria patients. Clinical guidelines for the management of Plasmodium falciparum include the use of a dose of primaquine phosphate resulting intolerable side effects. Therefore, the aim of this work was to formulate primaquine phosphate-loaded PLGA nanoparticles by using a nanoprecipitation method in order to increase its bioavailability to minimize drug intake. This leads to reduced toxicity and better therapeutic efficacy of the drug. The synthesized nanoparticles were characterized by using dynamic light scattering (DLS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), Fourier transformed infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and powder X-ray diffraction (XRD). TEM analysis revealed the presence of smooth spherical-shaped nanoparticles. The drug DLS analysis confirmed the presence of negatively charged nanoparticles with particle size in the range of 100-400 nm. The drug release study was performed to analyses different kinetic models like zero-order model, first-order model, Higuchi model, Hixson-Crowell model, and Korsmeyer-Peppas model.